Approaches to the University Bibliographical Heritage of the Universidad de Matanzas (Palimpsesto, 2024)
The proposed topic responds to a doctoral research that is derived from the line of research that contributes to the project "Cultural heritage and training: University cultural heritage (PCU), history, heritage education and local development" is a current topic because it delves into an aspect little studied, but of great significance for universities: their libraries, the university bibliographic heritage and the scientific culture of the teachers. In this sense, the research aims to implement actions that contribute to the socialization of the university bibliographic heritage for the formation of the scientific culture of the teachers of the University of Matanzas
Keywords: University library; scientific culture; vocational training; university bibliographic heritage; University of Matanzas